The Relevansi Pemikiran Buya Hamka terhadap Tantangan Pendidikan Islam - Afifah Nur Azizah; Dzulkifli Hadi Imawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to examine the relevance of Buya Hamka’s educational thought in addressing the challenges of the digital era. The rapid advancement of technology has shifted the direction of education to become more technical and pragmatic, often neglecting the moral and spiritual dimensions that are, in fact, the core of true education. In this context, Buya Hamka’s ideas are considered highly relevant as they offer solutions grounded in universal Islamic values. This study focuses on key educational principles emphasized by Hamka, such as the strengthening of spirituality, the cultivation of noble character, guided intellectual freedom, the balance between worldly and spiritual life, and the vital role of teacher exemplarity in the educational process. This research employs a qualitative descriptive method with a library research approach, analyzing Hamka’s major works such as Falsafah Hidup and Tasawuf Modern, alongside relevant academic references. The findings indicate that Hamka’s educational ideas remain highly relevant and can serve as a philosophical foundation for building meaningful, value-oriented, and contextually responsive educational systems in the face of digitalization.